Regulating the catalytic activity of multi-Ru-bridged polyoxometalates based on differential active site environments with six-coordinate geometry and five-coordinate geometry transitions. Issue 17 (26th April 2021) - Li, Huafeng; Chen, Wenjing; Zhao, Yujie; Zou, Yan; Zhao, Xue; Song, Junpeng; Ma, Pengtao; Niu, Jingyang; Wang, Jingping
Abstract : Robust multi-Ru-bridged POMs have demonstrated strong capabilities in achieving oxidation catalysis. Further investigations indicate that the catalytic efficiency could be further optimized by tuning the geometry of the catalytic sites. Abstract : Five-coordinate geometry around ruthenium with highly exposed active sites has attracted intensive scientific interest due to its superior properties and extensive applications. Herein, we report a series of structurally controllable multi-Ru-bridged polyoxometalates, K5 NaH10 [{Ru4 (H2 O) n }(WO2 )4 (AsW9 O33 )4 ]· m H2 O {1, 1-dehyd-373K, 1-dehyd-473K, 1-dehyd-573K ; n = 4, m = 36; n = 4, m = 6; n = 4, m = 0; n = 0, m = 0} fabricated through a feasible assembly strategy using arsenotungstate {2, KNa12 H17 Cl2 (As4 W40 O140 )·29H2 O} as a structure-directing unit. Systematic characterization methods identified that the six-coordinate geometry can successfully transform into five-coordinate geometry about active sites (Ru) by removing aqua ligands under high reaction temperatures. All the multi-Ru-bridged polyoxometalates demonstrated strong stability and catalytic effectiveness in the transformation of 1-(4-chlorophenyl)ethanol to 4′-chloroacetophenone under very mild conditions. 1-dehyd-573K, specifically, achieves the best catalytic effectiveness with a turnover frequency (TOF) = 25 100·h −1 owing to its unique five-coordinate geometry on the Ru sites. To our knowledge, 1-dehyd-573K outperforms other POM-based catalysts in the oxidative catalysis of 1-(4-chlorophenyl)ethanol. The heterogeneous polyoxometalates were also proven to be strongly reusable, with their structural integrities well maintained after multiple-cycle catalytic reactions.